Вибір та економічне оцінювання стратегії конкуренції промислових підприємств в умовах іноземного інвестування - Баглай, Ірина Євгенівна (Національний університет "Львівська політехніка", 2018)
Дисертацію присвячено вирішенню наукового і прикладного завдання щодо вибору та економічного оцінювання стратегії конкуренції промислового підприємства в умовах іноземного інвестування. Розроблено типологізацію стратегічних підходів щодо приходу іноземного інвестора на промислове підприємство, на основі якої розроблено типологізацію змін, які здійснюють іноземні інвестори після приходу на вітчизняні промислові підприємства. Удосконалено порядок кадрового забезпечення промислових підприємств в умовах іноземного інвестування. Також удосконалено автором модель економічного оцінювання стратегії конкуренції промислового підприємства з іноземними інвестиціями. Удосконалено порядок вибору та реалізації стратегії конкуренції промислових підприємств з іноземними інвестиціями. Розвинуто метод збалансованих показників економічного оцінювання стратегії конкуренції промислових підприємств в умовах іноземного інвестування. Диссертация посвящена решению научного и прикладного задания по выбору и экономической оценки стратегии конкуренции промышленного предприятия в условиях иностранного инвестирования. Разработано типологизацию стратегических подходов к приходу иностранного инвестора на промышленное предприятие, на основе которой разработано типологизацию изменений, которые осуществляют иностранные инвесторы после прихода на отечественные промышленные предприятия. Усовершенствован порядок кадрового обеспечения промышленных предприятий в условиях иностранного инвестирования. Также усовершенствована автором модель экономической оценки стратегии конкуренции промышленного предприятия с иностранными инвестициями. Усовершенствован порядок выбора и реализации стратегии конкуренции промышленных предприятий с иностранными инвестициями. Развит метод сбалансированных показателей экономической оценки стратегии конкуренции промышленных предприятий в условиях иностранного инвестирования. The dissertation is devoted to solving a scientific and practical problem of choice and economic evaluation of competition strategy of industrial enterprises under conditions of foreign investment. The competition of industrial enterprise in the terms of foreign investment is the object of research. The theoretical, methodological and applied bases of selection and economic evaluation of competition strategy of industrial enterprise under conditions of foreign investment are the subject of the dissertation. In the first chapter "Theoretical and practical bases of choice of competition strategy of industrial enterprise under conditions of foreign investment", the selection of competition strategy of industrial enterprise in modern conditions is characterized, the features of foreign investment of industrial enterprises are explored and the influence of foreign investor on the development of competition strategy of domestic enterprises is researched. In the dissertation the typology of strategic approaches to arrival of foreign investor to industrial enterprise is developed. Among these strategic approaches, it is necessary to indicate: absorption; rebranding and production under their own brand and trade mark; investing in development and modernization without significant brand change; liquidation of potential competitor through bankruptcy. Based on this typology, the author developed typology of changes made by foreign investors after their coming to domestic industrial enterprises. Taking into account the changes in the functional areas of activity of enterprise will enable the investor to increase the speed and effectiveness of strategic decisions making about the changes in the following areas: production, marketing, personnel management, finance, logistics, information provision, organizational and managerial changes. In the dissertation the order of personnel support of industrial enterprises under conditions of foreign investment is improved which takes into account the formation of criteria and requirements for innovative active personnel and innovative inactive personnel. This order is recommended for use to managers of domestic industrial enterprises and personnel services in order to increase the efficiency level of personnel support. In the second chapter "Economic evaluation of activity and strategies of industrial enterprises with foreign capital", the estimation of foreign investments market of Ukraine is realized and its perspectives are characterized. In addition, the dissertation presents the results of marketing research of factors determining the competition strategies of industrial enterprises with foreign capital and factors of selection and implementation of competition strategies of industrial enterprise in conditions of foreign investment. According to the results of survey of eight companies, the functioning of domestic industrial enterprises on the basis of attracting foreign capital has the following advantages: significant financing that promotes the development of business entity, use of modern production technologies, modernization of fixed assets of enterprise, improvement of working conditions for employees, access to hard-to-reach sources of raw materials and resources, access to new markets. The situation when enterprise functions with foreign business principles without taking into account Ukrainian features, which may lead to imperfection of competition strategy of enterprise, problems in personnel management, etc. is identified among the disadvantages. In the third chapter "Strategic decisions of industrial enterprises and their economic evaluation in conditions of foreign investment", the mechanism of justification of competition strategy of industrial enterprise in terms of foreign investment is proposed, the approaches to economic evaluation of this strategy and the technology of forming strategic decisions in functional areas in accordance with the chosen competition strategy are defined. In the dissertation the order for selection and implementation of competition strategy of industrial enterprises with foreign investments is improved. It involves determining the criteria for choosing competition strategy of enterprise in terms of foreign investment and economic evaluation of implemented competition strategy. This order can be used by foreign top managers independently or together with domestic top managers, depending on the level of integration of foreign investor in management process of Ukrainian business entity. In addition, the method of balanced indicators of economic evaluation of competition strategy of industrial enterprises in the conditions of foreign investment is developed which adds such functional blocks as organizational culture, organizational structure, corporate social responsibility to balanced scorecard method of Norton and Kaplan, which enables top managers to take into account the peculiarities of functioning of domestic industrial enterprises under conditions of foreign investment. The author proposes to conduct the economic evaluation of competition strategy of industrial enterprise with foreign capital via estimation of all functional blocks by using the method of balanced indicators. Therefore, the model of economic evaluation of competition strategy of industrial enterprise with foreign investment is improved, it based on calculation of proposed integral indicator that takes into account the efficiency of strategy by functional blocks: "Finance", "Internal business processes", "Customers", "Education and development", "Organizational culture", "Organizational structure", "Corporate social responsibility". The proposed model allows top managers and foreign investors to evaluate the effectiveness of competition strategies of enterprises with foreign investments and to determine the deviation of some indicators for their effective and timely elimination. Beside this, the economic evaluation of the competition strategy of LLC «Leoni wiring systems UA GmbH» was realized by using proposed model.
Выбор и экономическое оценивание стратегии конкуренции промышленных предприятий в условиях иностранного инвестирования
The choice and economic evaluation of industrial enterprises competition strategy under conditions of foreign investment
Keywords: стратегія конкуренції; іноземні інвестиції; інвестор; ефективність; оцінювання; промислове підприємство; страстратегия конкуренции; иностранные инвестиции; инвестор; эффективность; оценка; промышленное предприятие; competition strategy; foreign investment; investor; efficiency; evaluation; industrial enterprise; 005.21:339.137.2:338.45